THE SOCIAL-GOSPEL NOVELISTS’ CRITICISMS OF AMERICAN SOCIETY & THE BIBLIOGRAPHY OF SOCIAL-GOSPEL NOVELS - Suderman, Elmer F. (American Studies, 1966)
THE SOCIAL-GOSPEL NOVELISTS’ CRITICISMS OF AMERICAN SOCIETY & THE BIBLIOGRAPHY OF SOCIAL-GOSPEL NOVELS